The last full moon lessons on my life - Fernando, Gilda Cordero (University of the Philippines Press GCF Books, 2005)
"In this colorful memoir marking her 75th birth year, story-teller par excellence Gilda Cordero-Fernando gathers the stories of her life--written, she says, while she "can still remember." Then she playfully promises "not to tell all." Her galactic journey filled with gifts and synchronicities, misadventures and paradoxes, takes us from her ancestral roots in provincial gentry to behind-the-scenes of Manila's elite literary circles; from political protest to intimations of past lives and communications with the other side; from art-filled family rituals to Gilda's Living Will. Ever-optimistic, often hilarious, and always stunningly honest, Gilda Cordero-Fernando inspires us with her fearless view of life and soothes with the healing power of memory.--Mariel N. Francisco"--Back cover.